Peluang dan Tantangan Indonesia-Australia Comprehensive Strategic Partnership Pasca Terbentuknya Kerja Sama Pertahanan Trilateral AUKUS - Pradono Budi Saputro; A. Kurniawan Ulung; Muhammad Abdurrohim; Al Hafizh (Universitas Diponegoro, 2024)
Indonesia and Australia are neighboring countries with fluctuate bilateral relations. In 2018, they formed Indonesia-Australia Comprehensive Strategic Partnership (IA-CSP) to enhance their partnerships in strategic sectors for the stability of regional security in the Indo-Pacific. However, the problem came up in 2021 when Australia established trilateral defense cooperation AUKUS with the United Kingdom and the United States. This cooperation facilitates Australia to have nuclear-powered submarines to strengthen its military power. This cooperation has raised the eyebrows of Indonesia as it is against IA-CSP’s pillars, particularly pillar on securing the two countries and the region’s shared interest, and pillar on contributing to Indo-Pacific stability and prosperity. Therefore, Indonesia regretted Australia’s participation in AUKUS because the former deemed the latter to have violated its commitment on IA-CSP. This research aims to analyze IA-CSP’s opportunities and challenges post-establishment of AUKUS. It used a qualitative method, with interviews and literature review in place to collect data. The authors used regional security complex theory and strategic partnership concept for analysis. This research found that AUKUS does not disrupt the implementation of IA-CSP because the cooperation instead provides opportunities that Indonesia can utilize for its national interest. However, AUKUS poses challenges that Indonesia needs to tackle.